The Psychopathology of Worthlessness in Depression - Harrison, Phillippa; Lawrence, Andrew J.; Wang, Shu; Liu, Sixun; Xie, Guangrong; Yang, Xinhua; Zahn, Roland (Frontiers in Psychiatry, 2022)
Background| Despite common dissatisfaction with the syndromic heterogeneity of major depression, investigations into its symptom structure are scarce. Self-worthlessness/inadequacy is a distinctive and consistent symptom of major depression across cultures. Aims| We investigated whether self-worthlessness is associated with self-blaming attribution-related symptoms or is instead an expression of reduced positive feelings overall, as would be implied by reduced positive affect accounts of depression. Methods| 44161 undergraduate students in Study 1, and 215 patients with current Major Depressive Disorder (MDD) and 237 age-matched healthy control participants in Study 2 completed the well-validated Symptom Check List-90. Depression-relevant items were used to construct regularised partial correlation networks with bootstrap estimates of network parameter variability. Results| Worthlessness co-occurred more strongly with other symptoms linked to self-blaming attributions (hopelessness, and self-blame), displaying a combined edge weight with these symptoms which was significantly stronger than the edge weight representing its connection with reduced positive emotion symptoms (such as reduced pleasure/interest/motivation, difference in edge weight sum in Study 1=2.95, in Study 2=1.64; 95% confidence intervals: Study 1: 2.6-3.4; Study 2: 0.02-3.5; Bonferroni-corrected p<.05). Conclusions| This confirms the prediction of the revised learned helplessness model that worthlessness is most strongly linked to hopelessness and self-blame. In contrast, we did not find a strong and direct link between anhedonia items and a reduction in self-worth in either study. This supports worthlessness as a primary symptom rather than resulting from reduced positive affect.